Analysis of Motor Function in the Tg4-42 Mouse Model of Alzheimer’s Disease - Wagner, Jannek M.; Sichler, Marius E.; Schleicher, Eva M.; Franke, Timon N.; Irwin, Caroline; Löw, Maximilian Johannes; Beindorff, Nicola; Bouter, Caroline; Bayer, Thomas A.; Bouter, Yvonne (Frontiers in Behavioral Neuroscience, 2019)
Hallmarks of AD are memory impairments and cognitive deficits, but non-cognitive impairments, especially motor dysfunctions are also associated with the disease and may even precede classic clinical symptoms. With an aging society and increasing hospitalization of the elderly, motor deficits are of major interest to improve independent activities in daily living. Consistent with clinical findings, a variety of AD mouse models develop motor deficits as well. We investigated the motor function of 3 and 7-months-old Tg4-42 mice in comparison to wild-type controls and 5XFAD mice and discuss the results in context with several other AD mouse model. Our study shows impaired balance and motor coordination in aged Tg4-42 mice in the balance beam and rotarod test, while general locomotor activity and muscle strength is not impaired at 7 months. The cerebellum is a major player in the regulation and coordination of balance and locomotion through practice. Particularly, the rotarod test is able to detect cerebellar deficits. Furthermore, supposed cerebellar impairment was verified by 18F-FDG PET/MRI. Aged Tg4-42 mice showed reduced cerebellar glucose metabolism in the 18F-FDG PET. Suggesting that, deficits in coordination and balance are most likely due to cerebellar impairment. In conclusion, Tg4-42 mice develop motor deficits before memory deficits, without confounding memory test. Thus, making the Tg4-42 mouse model a good model to study the effects on cognitive decline of therapies targeting motor impairments.